2012
DOI: 10.3141/2269-13
|View full text |Cite
|
Sign up to set email alerts
|

Status Quo of City Logistics in Scientific Literature

Abstract: Roadway infrastructure is reaching maximum capacity in urban areas because of expanding urbanization, demographic changes, and continuously increasing freight volumes. An overview of the latest research on city logistics is needed to address these challenges, and a review of the scientific literature is presented. A specifically designed framework for systematic literature review was used to analyze 92 relevant articles from prominent electronic databases. A taxonomy of city logistics literature was created to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
(62 reference statements)
0
25
0
1
Order By: Relevance
“…The synonyms came from lists in Browne et al (2005) and Wolpert and Reuter (2012). The search included only peerreviewed journal articles to ensure a high standard among the identified articles, a method used by e.g.…”
Section: Selectionmentioning
confidence: 99%
“…The synonyms came from lists in Browne et al (2005) and Wolpert and Reuter (2012). The search included only peerreviewed journal articles to ensure a high standard among the identified articles, a method used by e.g.…”
Section: Selectionmentioning
confidence: 99%
“…It can also assist in achieving sustainability goals by decreasing the number of vehicles entering the city. Despite the theoretical advantages of UCCs, most initiatives were terminated within a few years (Quak 2008) because of limited usage, the cost of the additional transhipment, drop back of the initial governmental subsidies, wrong location choice, wrong type of vehicle and/ or bad organisation of the UCC (Browne et al 2005;Marcucci, Danielis 2008;Van Duin et al 2010;Wolpert, Reuter 2012;Olsson, Woxenius 2014). To understand the reason behind low volumes, it is important to understand this variability in perspectives towards UCCs among stakeholders in the urban freight domain.…”
Section: Uccs In the Netherlandsmentioning
confidence: 99%
“…Review of the available literature on city logistics revealed several terms and interpretations used to investigate this concept (Wolpert & Reuter, 2012); therefore, the city logistics should be considered in the broadest concept:…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, so far, only a few models have been proposed with regard to mathematical modeling of city logistics, and even the proposed models have not been properly developed (Saeedi et al, 2017). In terms of reviewing, investigating, and identifying the related literature as well as modeling in the field of city logistics, several review studies have been provided by different researchers, including Anand et al (2012), Taniguchi et al (2014), Anand et al (2015), Muñuzuri and Pablo (2012) and Wolpert and Reuter (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation